The Effect of Social Media and Word Of Mouth on Purchase Decisions at the MayShopping Store - Asyifa Atma; Sri Ernawati (Basic and Applied Accounting Research Journal, 2022)
This researcher aims to examine the influence of social media and word of mouth on purchasing decisions at the MayShopping store. This study aims to determine the effect of social media and word of mouth on purchase decisions at the MayShopping store. The method of collecting data in this study was carried out by distributing questionnaires to 96 consumers of MayShopping store respondents. The research method used is the associative method. Data analysis uses validity test, reliability test, classic assumption test, multiple linear regression test, correlation coefficient test, coefficient of determination test, T test and F test. The results of this study indicate that Social Media has a significant effect on purchase decisions with a calculated t value of 9.215 > 1.661 and a significant 0.000 <0.05. Word of Mouth has a significant effect on purchase decisions with a tcount of 3.056 > 1.661 and a significant 0.003 <0.05. Social Media and Word Of Mouth together have a significant effect on purchase decisions with a Fcount of 13.053 > 3.99 and a significant value of 0.000 <0.05.